Employee reward structures - Anderson, Jackie (Spiramus Press Ltd, 2017)
This is a comprehensive guide to the tax treatment of executive reward packages, from recruitment to termination. Includes a comprehensive glossary of terms, checklists and flowcharts. The sixth edition contains analysis of: the following changes:Taxation of pensions contributions, cap on tax relief for contributions, additional rate relief restriction, alignment of pension input periods, reduction in lifetime allowance, freedom to draw down lump sumsTermination payments Significant proposed changes in treatmentEmployee Benefit Trusts: Important case law developments (Murray Group Holdings)Employee Shareholder Shares: Changes to the relief and proposal to end agreementsEmployee Share Plans: Streamlining and Self-certificationBenefits in kind: Removal of 'lower-paid employee' statusIncludes complete work on CD-ROM (with cross-references and website resources hyperlinked) with the printed book.